2011
DOI: 10.1080/09593330.2011.565078
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the removal efficiency of refractory dissolved organic matter in wastewater treatment plants using a fluorescence technique

Abstract: The spectroscopic characteristics and relative distribution of refractory dissolved organic matter (R-DOM) in sewage have been investigated using the influent and the effluent samples collected from 15 large-scale biological wastewater treatment plants (WWTPs). Correlation between the characteristics of the influent and the final removal efficiency was also examined. Enhancement of specific ultraviolet absorbance (SUVA) and a higher R-DOM distribution ratio were observed for the effluent DOM compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Indeed, we showed that simple OM (protein-like fluorescence) was found in the most bioaccessible fractions (DOM and EPS) while the least bioaccessible ones (HLS and the non-extractable residue) contained significant amounts of complex and refractory OM (glycated protein-like, ligno-cellulosic-like and lipofuscin-like fluorescence). These results were consistent with those previously reported in the literature dealing with the evolution of fluorescence fingerprints in the water line of wastewater treatment: usually, fluorescence due to simple organic materials predominated in the raw sewage and drastically decreased in the effluent while the fluorescence due to complex organic materials persisted in the effluent or increased compared to the raw sewage (Hur et al, 2011). However, in the present work, protein-like fluorescence was systematically found in the fractions excepted in the non-extractable residue.…”
Section: Samplesupporting
confidence: 94%
“…Indeed, we showed that simple OM (protein-like fluorescence) was found in the most bioaccessible fractions (DOM and EPS) while the least bioaccessible ones (HLS and the non-extractable residue) contained significant amounts of complex and refractory OM (glycated protein-like, ligno-cellulosic-like and lipofuscin-like fluorescence). These results were consistent with those previously reported in the literature dealing with the evolution of fluorescence fingerprints in the water line of wastewater treatment: usually, fluorescence due to simple organic materials predominated in the raw sewage and drastically decreased in the effluent while the fluorescence due to complex organic materials persisted in the effluent or increased compared to the raw sewage (Hur et al, 2011). However, in the present work, protein-like fluorescence was systematically found in the fractions excepted in the non-extractable residue.…”
Section: Samplesupporting
confidence: 94%
“…The biodegradability of organic matter is an important factor for evaluating both the treatability of organic matter in wastewater treatment plants and biogeochemical roles of effluents in the receiving water [7,9]. It is also related to various features of organic matter, such as the molecular weight [40], the N:C ratio [41] and the fraction of protein-like materials [10,29,31].…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradability is the most critical factor when evaluating the removal performances of many wastewater treatment plants primarily relying on biological processes [9]. The degree of biodegradability is also closely related to biogeochemical and ecological impacts of effluents on the receiving water [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradability determines the sustainability and suitability of wastewater for further treatment. 26 Dhanke and Wagh 27 reported that increasing the biodegradability index is good for biological degradation of wastewater. Nagar and Devra 28 stated that the use of advanced oxygen processes will increase the biodegradability of textile wastewater by using silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%